Strategi Evaluasi Terbaik Menghadapi Kompleksitas UTS di Lembaga Pendidikan - Ilham Hidayat; Muhammad Rizqi Robbani; Arrasyidin Arrasyidin (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to describe and analyze the implementation of structured and unstructured midterm exams (daily tests) in two different schools. The selection of the right evaluation method is a determining factor in assessing learning outcomes. The selection of the right evaluation method plays a crucial role in assessing learning outcomes. In the face of the complexity of unstructured evaluation, it is important to understand how educational institutions can develop and implement effective evaluation strategies. This study used a qualitative approach with a case study research type (Case Study) with a research focus in two different institutions. Data collection was carried out by observation, interviews, and documentation. The results of the study showed that structured midterm exams and unstructured midterm exams have their own advantages and disadvantages. Structured midterm exams can provide more accurate and accountable test results. However, structured midterm exams can make it difficult for students to understand the material presented by the teacher. On the other hand, unstructured midterm exams can encourage students' enthusiasm and diligence. However, unstructured midterm exams can make students stressed and anxious because they do not know when the midterm exam will be held.